2020
DOI: 10.1039/c9fo02690h
|View full text |Cite
|
Sign up to set email alerts
|

Screening of by-products from the food industry as growth promoting agents in serum-free media for skeletal muscle cell culture

Abstract: Hydrolysates from food by-products allow higher cell growth and metabolic activity than commercially available serum in skeletal muscle cell culture and can potentially be used to produce a tailor-made serum-free media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…Although substantial progress has been achieved in recent years by both for‐profit companies and academic groups, CM remains a relatively new area of investigation. As might be expected for a nascent field that draws heavily on knowledge gained from previous work aimed at a distinct set of problems, review, and perspective papers about CM (at least 50 by our estimate) [ 10–14,16,18,23,28,37,44,64–109 ] currently outnumber original research papers where CM production is the primary intended application (at least 24) [ 15,59,110–131 ] or CM‐related patents (at least 24). [ 132–155 ] These estimates do not include LCA or TEA studies, consumer acceptance studies, or purely computational analyses.…”
Section: Cultivated Meatmentioning
confidence: 93%
“…Although substantial progress has been achieved in recent years by both for‐profit companies and academic groups, CM remains a relatively new area of investigation. As might be expected for a nascent field that draws heavily on knowledge gained from previous work aimed at a distinct set of problems, review, and perspective papers about CM (at least 50 by our estimate) [ 10–14,16,18,23,28,37,44,64–109 ] currently outnumber original research papers where CM production is the primary intended application (at least 24) [ 15,59,110–131 ] or CM‐related patents (at least 24). [ 132–155 ] These estimates do not include LCA or TEA studies, consumer acceptance studies, or purely computational analyses.…”
Section: Cultivated Meatmentioning
confidence: 93%
“…However, the potential cytotoxicity and safety of microbe-based hydrolysate used has not been thoroughly tested and remains a safety concern. In another study, pork plasma digested with Alcalase was shown to restore bovine skeletal muscle cell function and enhanced cell growth (Andreassen et al 2020 ). However, the use of animal-derived hydrolysate for CM production is counterintuitive to the purpose of being slaughter-free meat itself.…”
Section: The Use Of Hydrolysate In Animal Cell Culturementioning
confidence: 99%
“…Conditioned media systems have also been suggested as a solution to replace serum—the growth factors and other useful products that the cultivated meat cells produce themselves can be recycled and concentrated to support growth of other new cells in an interconnected system of bioreactors (Pawitan, 2014). As will be discussed in more detail in a later section, there is the possibility that plant or fungal protein extracts can function as homologs for important growth factors and other regulatory proteins in cultivated meat media, but this remains to be investigated fully (Andreassen, Pedersen, Kristoffersen, & Beate Rønning, 2020; Venâncio et al., 2003).…”
Section: Strategies For Serum‐free Media Formulationmentioning
confidence: 99%